Mengembangkan Tes Myer Briggs Type Indicator (MBTI) sebagai identifikasi awal untuk layanan konseling karir di SMK Negeri 1 Demak - Sri Wahyu Widayati; Yashinta Rizki Ananda (Ikatan Bimbingan dan Konseling Sekolah)
In order for effective career counseling services counselors should understand the personality type of each client. This study aims to develop the Myer Briggs Type Indicator (MBTI) test tool to support career counseling services in SMK. To answer the question is tested against the test tool to determine the validity and reliability. The results show that the test equipment is valid and reliable to support career counseling services in SMK.